PERALIHAN HAK ATAS TANAH TERKAIT PEMBAGIAN HAK BERSAMA BERDASARKAN PEWARISAN DI BPN KABUPATEN LIMAPULUHKOTA - Moula Ibra; Anggun Lestari Suryamizon; Mahlil Adriaman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Maintenance of land registration data is carried out when there is a change in the physical data or the data of the jurisdictional object of Land registration that has been registered The transfer of land rights can be through two ways, namely by switching through a legal event such as inheritance and transferred due to the existence of legal acts such as sharing of rights. As a result of the inheritance, the property belongs to the land. Based on the formula of the above problems, the purpose of this research is to know the process of management of the transfer of land rights related to the sharing of common rights based on inheritance and to know why the BPN of the Fifty City District uses APHB as the basis for transfer of inherited rights. The research method used by the authors in this study is descriptive, which is the research that focuses on solving the problem investigated by describing the state of the subject and the object based on apparent facts. The result of this research is that there are several factors or several things that cause the division of inheritance rights to be done with two processes first yaiu by descending inheritors first then using the Act of Common Division of Rights as the basis for the distribution of heritage rights.